2018
DOI: 10.1016/j.ajic.2017.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the patient experience of health care–associated infection: A qualitative systematic review

Abstract: The impact of different HAIs may vary; however, there are many similarities in the experience recounted by patients. The biosociocultural context of contagion was graphically expressed, with potential impact on social relationships and professional interactions highlighted. Further research to investigate contemporary patient experience in an era of antimicrobial resistance is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…There appears to be a reliance of ward based staff on "specialist" IPC staff providing information; however, patients may have to wait some days for this information, incurring uncertainty and anxiety in the process. This finding echoes that of a recent systematic review of patient experience of a range of other healthcare-associated infections and colonisation (Currie, Melone, et al, 2018), where included studies highlighted the frustration experienced by patients in trying to get information, from healthcare professionals, which met their needs. However, whereas our participants tended to perceive this as due to time pressures on staff, other studies on MRSA have reported a perceived lack of staff knowledge about the healthcare-associated infection (Criddle & Potter, 2006;Lindberg, Carlsson, Högman, & Skytt, 2009;Skyman, Sjöström, & Hellström, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…There appears to be a reliance of ward based staff on "specialist" IPC staff providing information; however, patients may have to wait some days for this information, incurring uncertainty and anxiety in the process. This finding echoes that of a recent systematic review of patient experience of a range of other healthcare-associated infections and colonisation (Currie, Melone, et al, 2018), where included studies highlighted the frustration experienced by patients in trying to get information, from healthcare professionals, which met their needs. However, whereas our participants tended to perceive this as due to time pressures on staff, other studies on MRSA have reported a perceived lack of staff knowledge about the healthcare-associated infection (Criddle & Potter, 2006;Lindberg, Carlsson, Högman, & Skytt, 2009;Skyman, Sjöström, & Hellström, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…Currie et al attempted to overcome this knowledge gap in their new study, which evaluated the emotional and physical responses of patients to HAIs, including SSIs; their experience with health care personnel; the effect on their day‐to‐day life, relationships, finances, and work; and the associated cultural factors (e.g., stigma linked to infection) . Patients with SSIs described a sudden onset of extreme pain and leakage from the incision site that resulted in emotional and physical stress, which occurred concurrently with the patient seeking answers for the problems they were experiencing.…”
Section: Patient Experiencementioning
confidence: 99%
“…Patients with SSIs described a sudden onset of extreme pain and leakage from the incision site that resulted in emotional and physical stress, which occurred concurrently with the patient seeking answers for the problems they were experiencing. These patients subsequently had concerns about the quality of their interactions with health care personnel, including feeling frustration with trying to obtain information from personnel and believing that personnel were dismissive …”
Section: Patient Experiencementioning
confidence: 99%
See 2 more Smart Citations